Tuberculosis of the chest wall without pulmonary involvement - Gaude G; Reyas A (Lung India, 2008)
Skeletal tuberculosis is usually seen in association with primary pulmonary form. Pulmonary tuberculosis of the chest wall is a rare entity. We herein report a case of tuberculosis of the chest wall without pulmonary involvement that presented with big ulcer in the anterior chest wall and responded completely to the antituberculosis therapy without any surgical intervention.